This is for you: Social modulations of proximal vs. distal space in collaborative interaction - Rocca, Roberta (Sci Rep, 2019)
Human spatial representations are shaped by affordances for action offered by the environment. A prototypical example is the organization of space into peripersonal (within reach) and extrapersonal (outside reach) regions, mirrored by proximal (this/here) and distal (that/there) linguistic expressions. The peri-/extrapersonal distinction has been widely investigated in individual contexts, but little is known about how spatial representations are modulated by interaction with other people. Is near/far coding of space dynamically adapted to the position of a partner when space, objects, and action goals are shared? Over two preregistered experiments based on a novel interactive paradigm, we show that, in individual and social contexts involving no direct collaboration, linguistic coding of locations as proximal or distal depends on their distance from the speaker’s hand. In contrast, in the context of collaborative interactions involving turn-taking and role reversal, proximal space is shifted towards the partner, and linguistic coding of near space (‘this’ / ‘here’) is remapped onto the partner’s action space.